2003
DOI: 10.1370/afm.23
|View full text |Cite
|
Sign up to set email alerts
|

Defining and Measuring Interpersonal Continuity of Care

Abstract: Future inquiry in family medicine should focus on better understanding the interpersonal dimension of continuity of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
490
0
42

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 442 publications
(553 citation statements)
references
References 83 publications
4
490
0
42
Order By: Relevance
“…[45][46][47][48] Continuity also has various components, including informational continuity (the availability of a patient's health information at the point of care), continuity with the same practice over time, and interpersonal continuity with the same clinician over time. 4,5,49,50 These last two aspects are the concepts most often referenced in primary care research; they have been associated with lower hospitalization rates, [51][52][53][54][55][56] lower complication rates for patients with chronic conditions, 55 fewer emergency room visits, 57,58 lower total costs 53 and lower episodebased costs for chronic conditions. 54,55,59,60 Greater site and interpersonal continuity are also associated with increased use of preventive services and guideline-concordant care.…”
Section: Primary Care Features and Associations With Patient Outcomesmentioning
confidence: 99%
“…[45][46][47][48] Continuity also has various components, including informational continuity (the availability of a patient's health information at the point of care), continuity with the same practice over time, and interpersonal continuity with the same clinician over time. 4,5,49,50 These last two aspects are the concepts most often referenced in primary care research; they have been associated with lower hospitalization rates, [51][52][53][54][55][56] lower complication rates for patients with chronic conditions, 55 fewer emergency room visits, 57,58 lower total costs 53 and lower episodebased costs for chronic conditions. 54,55,59,60 Greater site and interpersonal continuity are also associated with increased use of preventive services and guideline-concordant care.…”
Section: Primary Care Features and Associations With Patient Outcomesmentioning
confidence: 99%
“…We used two measures of continuity: the Number of Physicians Index (NPI), and the Usual Provider of Continuity (UPC) index. 7,8 The NPI, in this context, is the total number of unique authors of H&Ps and/or progress notes for a patient. The UPC is calculated as the largest number of notes written by a single physician divided by the total number of notes written for a patient.…”
Section: Predictor Variablesmentioning
confidence: 99%
“…Precisely in this context, clinicians point out a neglected distinction between provision of care (by clinicians) and receipt of care (by patients), 62 and the patient's noncompliance with or lack of adherence to recommended treatments is a plausible (albeit one-sided) explanation for the disconnect between provision and receipt of care. Researchers have found that continuity of care, allowing clinicians to establish and develop ongoing interactions that promote familiarity with their patients, is a fundamental dimension of quality care, 63,64 particularly for vulnerable patient populations. 65 Our investigation concurs with these findings; a clinician's interactional familiarity with a patient enables clinicians to deliver more effective and efficient person-focused care.…”
Section: Discussionmentioning
confidence: 99%